2007
DOI: 10.1189/jlb.1006640
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria-induced Gr-1+ subsets from distinct myeloid lineages have opposite effects on T cell expansion

Abstract: Similar to the regulation of vasodilation, the balance between NO and superoxide (O2-) regulates expansion of activated T cells in mice. Reduction of suppressive NO levels by O2- is essential for T cell expansion and development of autoimmunity. In mice primed with heat-killed Mycobacterium, a splenocyte population positive for Gr-1 (Ly-6G/C) is the exclusive source of both immunoregulatory free radicals. Distinct Gr-1+ cell subpopulations were separated according to Ly-6G expression. In culture with activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 45 publications
2
83
0
Order By: Relevance
“…Mature polymorphonuclear cells were not seen in these purified preparations. The heterogeneous nature of the Gr-1 ϩ CD11b ϩ cells has been documented before in infection (19,20,51) and in cancer (2,9,74). Flow cytometric analysis using forward scatter and side scatter showed that the sorting process yielded mostly live cells (Fig.…”
Section: Cd11bsupporting
confidence: 55%
See 1 more Smart Citation
“…Mature polymorphonuclear cells were not seen in these purified preparations. The heterogeneous nature of the Gr-1 ϩ CD11b ϩ cells has been documented before in infection (19,20,51) and in cancer (2,9,74). Flow cytometric analysis using forward scatter and side scatter showed that the sorting process yielded mostly live cells (Fig.…”
Section: Cd11bsupporting
confidence: 55%
“…Murine monocytes are composed of two distinct subpopulations characterized by expression or absence of Gr-1 (32,33). Gr-1 is expressed on neutrophils, inflammatory monocytes, and some populations of dendritic cells (69), and monoclonal antibodies to Gr-1 recognize both Ly6C and Ly6G isoforms (26 (20). In infections with Trypanosoma gondii, Listeria monocytogenes, or Aspergillus fumigatus, the monocytic component is required for an effective host response (17,21,35,37,54,58,59,61,62).…”
Section: Although the Monocytic Cd11bmentioning
confidence: 99%
“…In mycobacteria-induced experimental autoimmune encephalomyelitis models, CD11b + Gr1 + Ly-6G 2 cells are compartmentalized in spleen and prevent T cell expansion by secreting NO upon contact with Ag-activated T cells. NO-mediated suppression is counterbalanced by O 2 2 produced by neutrophils (45). These feedback mechanisms have major effects on experimental autoimmune encephalomyelitis pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The CD11b + Ly-6G + Ly-6C high cells with monocytic-like morphology are termed monocytic MDSCs (M-MDSCs), whereas the CD11b + Ly-6G + Ly-6C low cells have a granulocyte-like morphology and are termed granulocytic MDSCs (G-MDSCs) (9). These two cell groups differ in functionality: G-MDSCs frequently inhibit T cell function through arginase-1 (ARG-1) enzyme activity, whereas M-MDSCs more commonly inhibit T cell functions via nitric oxide (NO) production (10)(11)(12). Interferon (IFN)-γ-mediated activation of MDSCs results in the upregulation of ARG-1 and NO production.…”
Section: Origin and Subsets Of Mdscsmentioning
confidence: 99%